Spanish Healthcare Sector Management in the COVID-19 Crisis Under the Perspective of Austrian Economics and New-Institutional Economics - Sánchez-Bayón, Antonio; González-Arnedo, Esther; Andreu-Escario, Ángel (Frontiers in Public Health, 2022)
This is a study of Political Economy, Law & Economics, and Public Choice, applied to COVID-19 crisis management, and how the Spanish healthcare sector has operated under stressful conditions. Market and state failures are evaluated and some improvements are offered, according to the theories of Austrian Economics and New-Institutional Economics. At the macro level, the premise is the decentralization of the Spanish healthcare system a long time ago, to provide a better service to citizens, according to the idiosyncrasies of the Autonomous Communities (similar to federal states). The crisis has evidenced the failures of the Spanish system and its semi-federal model, without coordination to manage the trouble. Also, the General Government's recentralization attempt has failed too, proving Mises's theorem on the impossibility of economic calculation in intervened and coactive systems, with problems of shortages, lack of coordination, etc.; Buchanan-Tullock's theorem on the unfinished agenda of state interventionist and it suppression of private sector was also proven. At the micro level, health institutions (hospitals and health centers) have fallen into the paradox of media overexposure and the fake-news risk, because the more information they have tried to transmit, the more confusion they have caused, reducing the value of the supposed transparency and accountability, in addition to decreasing citizen wellbeing, giving way to a higher level of dissatisfaction and more risk of a syndemic. To perform the analysis of accountability and wellbeing perceived, this paper has used quantitative contrast techniques on secondary sources, such as the surveys of Centro de Investigaciones Sociológicas (part of the Public Sector) or Merco rankings (independent institution).